2017
DOI: 10.1016/j.lungcan.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of initial and intracranial failure in metastatic EGFR-mutant non-small cell lung cancer treated with erlotinib

Abstract: Objectives Patients with metastatic EGFR-mutant (mEGFRmt) NSCLC have favorable survival when treated with erlotinib. We hypothesized that treatment failure in most patients is limited to initial sites of disease, in which case incorporating local therapy such as radiation might further delay progression. We therefore analyzed patterns and predictors of failure in a large cohort of such patients. Materials and Methods We reviewed 189 patients treated with erlotinib for mEGFRmt NSCLC. We classified first patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 25 publications
(25 reference statements)
1
36
0
Order By: Relevance
“…In addition, among the 29 patients with brain metastases in the gefitinib arm, 12 relapsed after withdrawing from gefitinib therapy, and a recurrence peak occurred 5 to 10 months after gefitinib termination. This was also observed by Patel et al 27 who found that the occurrence of CNS metastasis increased sharply between 24 and 36 months in patients with EGFR mutations when treated with erlotinib. Therefore, EGFR-TKIs (such as gefitinib) may require long treatment duration to show efficacy, and adequate follow-up is required.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, among the 29 patients with brain metastases in the gefitinib arm, 12 relapsed after withdrawing from gefitinib therapy, and a recurrence peak occurred 5 to 10 months after gefitinib termination. This was also observed by Patel et al 27 who found that the occurrence of CNS metastasis increased sharply between 24 and 36 months in patients with EGFR mutations when treated with erlotinib. Therefore, EGFR-TKIs (such as gefitinib) may require long treatment duration to show efficacy, and adequate follow-up is required.…”
Section: Discussionsupporting
confidence: 79%
“…The baseline incidence of BM in EGFR -mutant NSCLC is similar to that of other oncogenic driver mutations, ranging from 23 to 32% ( 18 20 ). The cumulative incidence increases over time ( 19 , 21 ), with a 2-year actuarial risk of CNS progression of approximately 15–20% when patients received standard of care EGFR TKIs ( 21 , 22 ). BM development on EGFR TKI treatment is significantly more common among patients with baseline BM (2-year cumulative incidence of 47% among patients with pre-existing BM compared to 11% among those with no prior BM; p = 0.003) and correlates with a worse outcome ( 21 , 23 , 24 ).…”
Section: Egfr-mutant Nsclc Patientsmentioning
confidence: 99%
“…BM development on EGFR TKI treatment is significantly more common among patients with baseline BM (2-year cumulative incidence of 47% among patients with pre-existing BM compared to 11% among those with no prior BM; p = 0.003) and correlates with a worse outcome ( 21 , 23 , 24 ). Literature reporting the risk of cumulative incidence of brain progression according to EGFR mutation subtype is contradictory, some studies reporting higher cumulative risk among Del19- mutant tumors ( 21 ), and others among L858R -mutant tumors ( 22 , 24 ).…”
Section: Egfr-mutant Nsclc Patientsmentioning
confidence: 99%
“…17 Patients with EGFR mutated NSCLC had prolonged PFS and OS compared with those without EGFR mutation. 33 Concurrently, a separate report has shown no significant association between the number of metastases and patterns of initial PD in patients with EGFR-mutant NSCLC, 34 suggesting that a different approach might be required to explore the pattern of initial PD in EGFR tyrosine kinase inhibitors.…”
Section: Discussionmentioning
confidence: 99%